PENERAPAN MODEL TAKTIS DALAM PERMAINAN SEPAK BOLA GUNA MENINGKATKAN KETERAMPILAN BERMAIN - Oka Abdul Aziz; Firman Adityatama (Journal of Physical Education and Sport Science, 2020)
The purpose of this study is to know improving of playing skills, through the application of tactical models in the learning of football games in BAOK students. This research, the draft research looks at the initial conditions of students' skills in football including their knowledge and practice in the form of initial evaluation, subsequent treatment using tactical models, and finally a final evaluation to see the extent of the improvement in football skills after being given treatment.. The population of this study was 10 athletes. Sample determination uses total sampling technique with all athletes to be made a research subject. 14.3. Post Test results after being given student skills treatment there is a change to better and the result is 21.9. Based on the IBM-21 outputsSPSS table. It is known that the significance value of Asymp, Sig. (2-tailed) of 0.934 > 0.05.